Hormonal Receptor Modulation by Lipid Phytoconstituents: The Role of Monounsaturated Fatty Acids and Folate Derivatives from Persea americana in Endometrial Carcinogenesis Prevention - Barack Ndenga (Publisher, 2025)
Endometrial cancer stands among the most prevalent gynecologic malignancies globally, driven by multifactorial interactions between hormonal imbalance, lipid dysregulation, and genetic susceptibility. Despite advances in targeted therapies, the prevention and management of hormonally driven endometrial carcinogenesis remain challenging due to metabolic side effects and resistance mechanisms. This research introduces an innovative biochemical hypothesis suggesting that lipid-derived phyto-compounds from Persea americana (avocado) possess intrinsic capacities to modulate hormonal receptor dynamics and restore metabolic equilibrium at the cellular level. Leveraging AutoEvoChem™, a next-generation molecular modeling and quantum simulation platform developed by the author, we performed integrated computational analyses involving molecular docking, density functional theory (DFT), and hybrid molecular dynamics. These simulations focused on the interactions of monounsaturated fatty acids (MUFAs)—particularly oleic and palmitoleic acids—and folate derivatives (folate and 5-methyltetrahydrofolate) with the binding domains of the estrogen receptor (ERα) and progesterone receptor (PR-B). The computational results revealed a consistent pattern of receptor modulation. Oleic acid exhibited moderate but significant binding affinity to ERα, inducing partial destabilization of its active conformation and reducing ligand activation energy. In contrast, folate derivatives demonstrated high stability with PR-B, reinforcing its active conformation and enhancing its interaction with endogenous progesterone. When co-docked, oleic acid and folate formed a stabilized lipid–nucleotide complex that simultaneously downregulated ERα activation (−7.5 kcal/mol) and enhanced PR-B stability (−10.1 kcal/mol). Dynamic simulation trajectories (200 ns) demonstrated a synergistic biochemical effect: the MUFA–folate system reduced estrogenic hyperactivation by ~28% while increasing progesterone-dependent transcriptional regulation by ~33%. System-level modeling further revealed decreased activation of estrogen-responsive oncogenes (MYC, CCND1) and upregulation of tumor-suppressor pathways (TP53, PTEN), supporting a protective, anti-proliferative phenotype. Altogether, these findings point toward a novel mechanistic paradigm—the Hormonal Receptor Modulation Hypothesis (HRMH)—in which Persea americana-derived lipids and folate co-metabolites act as natural biochemical regulators of hormone receptors. Through lipid–nucleotide signaling crosstalk, these compounds contribute to membrane stability, receptor reprogramming, and homeostatic gene regulation, collectively mitigating the early molecular events of endometrial carcinogenesis. This study represents the first computational evidence that avocado’s monounsaturated fatty acids and folate derivatives may synergistically influence estrogen–progesterone receptor equilibrium, offering a biochemical rationale for nutritional cancer prevention. Beyond its biomedical implications, this work highlights the potential of AutoEvoChem™ as an AI-driven molecular exploration platform capable of elucidating complex biochemical interactions relevant to oncology and reproductive health.
This study investigates the hormonal receptor modulation potential of bioactive compounds derived from Persea americana (avocado), focusing on monounsaturated fatty acids (MUFAs) and folate derivatives in the context of endometrial carcinogenesis prevention. Using AutoEvoChem™, a novel molecular modeling and simulation platform developed by the author, we performed high-resolution docking, molecular dynamics, and systems biology simulations to explore ligand–receptor interactions with estrogen receptor alpha (ERα) and progesterone receptor B (PR-B). Results demonstrate that oleic acid partially inhibits ERα, while folate derivatives stabilize PR-B, producing a synergistic anti-proliferative effect. Molecular simulations also predict downstream regulation of tumor suppressor and estrogen-responsive genes, supporting the nutritional chemoprevention potential of avocado-derived compounds. This work introduces the Hormonal Receptor Modulation Hypothesis (HRMH) and showcases AutoEvoChem™ as a versatile tool for computational nutritional oncology research.